Monoallelic germline ATM mutation and organising pneumonia induced by radiation therapy to the breast. Issue 3 (4th February 2016) - Cordier, Jean-François; Cottin, Vincent; Lazor, Romain; Stoppa-Lyonnet, Dominique
Organising pneumonia is defined by the presence of intra-alveolar buds consisting of inflammatory cells, fibroblasts and myofibroblasts, and loose connective tissue, often associated with bronchiolitis obliterans. Organising pneumonia may be cryptogenic (idiopathic) or associated with a variety of causes including, especially, infection, adverse reaction to drugs, connective tissue diseases [1] and radiation therapy to the breast [2, 3]. Radiation-induced organised pneumonia may be associated with monoallelic ATM gene mutation http://ow.ly/WIpFe